2012
DOI: 10.1002/jib.27
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary research on wheat lipoxygenase during malting

Abstract: Characteristics of lipoxygenase (LOX) in wheat malt with various conditions, including optimum temperature, pH and thermostability, were studied. The results showed that the optimum temperature was 35 C, the optimum pH value was 6.8 and the deactivation temperature was 70 C. With increasing temperature, thermal stability was reduced. The LOX activity of dry wheat malt showed a significant positive correlation with filtration time (R = 0.979, p < 0.05). The LOX activity of the green malt showed a significant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A thermal pretreatment was applied to faba bean and lentil flours prior to mixing. Indeed, high temperatures (>70 °C) have previously been reported to be one of the ways to inactivate the lipoxygenase enzyme (Jayasena et al., 2010; Sun, Du, Jin, Liu, & Kong, 2012). Thermal pretreatment of lentil and faba flours led to a 12‐fold reduction in lipoxygenase activity in both legume flours (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…A thermal pretreatment was applied to faba bean and lentil flours prior to mixing. Indeed, high temperatures (>70 °C) have previously been reported to be one of the ways to inactivate the lipoxygenase enzyme (Jayasena et al., 2010; Sun, Du, Jin, Liu, & Kong, 2012). Thermal pretreatment of lentil and faba flours led to a 12‐fold reduction in lipoxygenase activity in both legume flours (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This is important since the losses of lutein can be significant during the storage of flour especially at high temperatures (Hidalgo & Brandolini, 2008) and during pasta and bread preparation (Hidalgo, Brandolini, & Pompei, 2010). High lipoxygenase (LOX) activity increases carotenoid losses (Hidalgo & Brandolini, 2012;Leenhardt, Lyan, Rock, Boussard, Potus, Chanliaud et al, 2006) with an optimum temperature for the wheat LOX of 35ºC (Sun, Du, Jin, Liu, Kong, 2012). Esterification is an interesting characteristic to improve the retention of lutein through the food chain since it increases lutein stability at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, after malting, the LOX activity decreased by 38.45% to 66.1%. Another study by our group found that the LOX was not resistant to the high temperature of the kiln (Sun et al, 2012). So reducing LOX activity in malt during the kilning process could contribute to the LOX activity decrease in wheat malts.…”
Section: Difference Analysis Of Tba Value Lox Activity Of Wheat and W...mentioning
confidence: 87%
“…As LOX activity was found to be influenced by the malting process (Kaukovirta-Norja et al, 1998), recently, the preliminary characteristics of wheat LOX during malting were studied by our group (Sun et al, 2012). Investigating the degree of proteolysis influence on LOX activity of wheat malt might be a good way to control the qualities of wheat malt, wort and beer.…”
Section: Effect Of Quality Parameters On Lipoxygenase Activity Of Whe...mentioning
confidence: 99%